Assessing the antibiotic susceptibility of freshwater Cyanobacteria spp. - Dias, Elsa; Oliveira, Micaela; Jones-Dias, Daniela; Vasconcelos, Vitor; Ferreira, Eugénia; Manageiro, Vera; Caniça, Manuela (Frontiers in Microbiology, 2015)
Freshwater is a vehicle for the emergence and dissemination of antibiotic resistance. Cyanobacteria are ubiquitous in freshwater, where they are exposed to antibiotics and resistant organisms, but their role on water resistome was never evaluated. Data concerning the effects of antibiotics on cyanobacteria, obtained by distinct methodologies, is often contradictory. This emphasizes the importance of developing procedures to understand the trends of antibiotic susceptibility in cyanobacteria. In this study we aimed to evaluate the susceptibility of four cyanobacterial isolates from different genera (Microcystis aeruginosa, Aphanizomenon gracile, Chrisosporum bergii, Planktothix agradhii), and among them nine isolates from the same specie (M. aeruginosa) to distinct antibiotics (amoxicillin, ceftazidime, ceftriaxone, kanamycine, gentamicine, tetracycline, trimethoprim, nalidixic acid, norfloxacin). We used a method adapted from the bacteria standard broth microdilution. Cyanobacteria were exposed to serial dilution of each antibiotic (0.0015-1.6 mg/L) in Z8 medium (20 ± 1 ºC; 14/10 h L/D cycle; light intensity 16 ± 4 µEm-2 s-1). Cell growth was followed overtime (OD450nm/microscopic examination) and the minimum inhibitory concentrations (MICs) were calculated for each antibiotic/isolate. We found that -lactams exhibited the lower MICs, aminoglycosides, tetracycline and norfloxacine presented intermediate MICs; none of the isolates were susceptible to trimethoprim and nalidixic acid. The reduced susceptibility of all tested cyanobacteria to some antibiotics suggests that they might be naturally non-susceptible to these compounds, or that that they might became non-susceptible due to antibiotic contamination pressure, or to the transfer of genes from resistant bacteria present in the environment.